Preserving a transforming tradition: Modifications in the Nyadran Tradition in Pacekulon Village, Pace District, Nganjuk Regency - Inna Havidatus Saniyah; Dhoni Zustiyantoro (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Nyadran remains a persistent tradition in Pacekulon Village, Pace Subdistrict, Nganjuk Regency, despite modifications made due to the Covid-19 pandemic in 2020. This study aims to identify the factors influencing the transformation of the traditional nyadran procession in Pacekulon Village post-Covid-19 and explain how these changes affected the community's life outlook. An ethnographic approach was used, which was conducted from February to July 2024. Data collection involved observations and structured interviews with 10 informants, including village heads, traditional stakeholders, and event participants. Data were analysed using an interactive model. The research identified pre-pandemic nyadran activities: 1) buffalo slaughter, 2) puppets, 3) teaching, 4) recitation, 5) bazaar, and 6) kirab and kroyokan tumpeng. Post-pandemic changes reduced these to: 1) recitation, 2) hike, and 3) kirab and kroyokan tumpeng. Factors affecting this transformation include the vacant village head position, health protocols, and economic conditions during the recovery period. The altered nyadran procession influenced the community's outlook, increasing awareness of unity, adapting priority scales, and strengthening beliefs in the tradition's impact on the social order. This research contributes to cultural anthropology and sociology by analysing the dynamics of the Nyadran procession changes within the Pacekulon community context. The findings can be applied to public policy development, community programs, and research on traditional preservation practices.   Tradisi nyadran tetap bertahan di Desa Pacekulon, Kecamatan Pace, Kabupaten Nganjuk, meskipun mengalami perubahan akibat pandemi Covid-19 pada tahun 2020. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang memengaruhi transformasi prosesi tradisi nyadran di Desa Pacekulon pasca Covid-19 dan menjelaskan bagaimana perubahan tersebut memengaruhi pandangan hidup masyarakat. Pendekatan etnografi digunakan, yang dilakukan dari Februari hingga Juli 2024. Pengumpulan data dilakukan melalui observasi dan wawancara terstruktur dengan 10 informan, termasuk kepala desa, pemangku adat, dan peserta acara. Data dianalisis dengan menggunakan model interaktif. Penelitian ini mengidentifikasi kegiatan-kegiatan nyadran sebelum pandemi: 1) Penyembelihan kerbau; 2) wayang; 3) pengajaran; 4) pengajian; 5) bazar; dan 6) kirab dan kroyokan tumpeng. Perubahan pasca pandemi mengurangi kegiatan-kegiatan tersebut menjadi: 1) pengajian, 2) jalan santai, dan 3) kirab dan kroyokan tumpeng. Faktor-faktor yang mempengaruhi perubahan ini antara lain kekosongan jabatan kepala desa, protokol kesehatan, dan kondisi ekonomi pada masa pemulihan. Prosesi nyadran yang berubah memengaruhi cara pandang masyarakat, meningkatkan kesadaran akan persatuan, mengadaptasi skala prioritas, dan memperkuat keyakinan akan dampak tradisi terhadap tatanan sosial. Penelitian ini memberikan kontribusi pada antropologi budaya dan sosiologi dengan menganalisis dinamika perubahan prosesi nyadran dalam konteks masyarakat Pacekulon. Temuan penelitian ini dapat diaplikasikan dalam pengembangan kebijakan publik, program-program komunitas, dan penelitian tentang pelestarian tradisi.